Perspektif Ekonomi Islam Dalam Pembiayaan Akad Murabahah di Koperasi Syariah Annajah Solution Indonesia - Hanifah Hanifah; Evi Novita (Economic Reviews Journal, 2023)
Ba’i murabahah is a sale and purchases agreement of an item by confirming the purchase price to the buyer, and the buyer pays more as profit. Murabahah is a popular product in Annajah Solution Indonesia sharia cooperatives, this study aims to find out how the murabahah financing system and how the islamic economic perspective in murabahah contract financing, is it in accordance with the concept of islmic economic by applying the Quran and Sunnah as the basic foundation of each activity. The results of the study show that murabahah financing system in the shariah cooperative of Annajah Solution has a predetermined procedure: 1) prospective customers must first become a member of the cooperative 2) customers have to wait 3 months to apply for financing. Islamic economic perspective in murabahah contract financing in shariah cooperative of Annajah Solution Indonesia is in accordance to the Islamic economic primciples and has been in accordance with fatwa DSN-MUI No 04/DSN-MUI/IV 2000 regarding murabahah, which is the contract implementation process, procurement of goods process, and murabahah bil wakalah process. Keywords:Islamic Economic, and Murabahah Financing